Capacity of the bovine intestinal mucus and its components to support Escherichia coli O157:H7 growth - C. Aperce; J. Heidenreich; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2010)
Escherichia coli O157:H7 contamination of human food products is a major concern for the beef industry. The pathogens responsible for outbreaks often originate from cattle, and E. coli O157:H7 can thrive in healthy cattle. To control contamination in the food chain, it is essential to understand how this pathogen is able to grow and compete with other bacteria in the gastrointestinal tracts of cattle. Previous studies have shown that bovine intestinal mucus supports bacterial colonization and can selectively influence makeup of the bacterial population. Intestinal mucus is made of mucins, which are gel-forming glycoproteins. Mucin molecules contain sialic acid that must be removed by neuraminidase enzyme to allow for complete degradation of mucin. E. coli O157:H7 lacks neuraminidase and should have little ability to degrade the complex mucin molecules. Our objective was to evaluate bovine intestinal mucus and its components in terms of their capacity to support E. coli O157:H7 growth in the presence or absence of feces and to understand the roles various enzymes play in this process.
Keywords: Cattlemen' s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen' s Day; Beef; Escherichia coli; Mucin; Pathogen